Dietary supplementation of fish protein hydrolysate in high plant protein diets modulates growth, liver and kidney health, and immunity of barramundi (Lates calcarifer) - Shoaib M Siddik; HD Pham; David Francis; BV Vo; M Shahjahan (2021)
Dietary supplementation of fish protein hydrolysate in high plant protein diets modulates growth, liver and kidney health, and immunity of barramundi (Lates calcarifer)